Antagonistic potential of endophytic bacteria from tomato seedlings - Viana, Milena Campos de Oliveira Alencar; Moura, Júlia Karoline Ferreira; de Lima, Maria Gabriela Gomes; Ribeiro, Igor Daniel Alves; Passaglia, Luciane Maria Pereira; Barreto, Marcos Cabral de Vasconcellos; Viégas, Pedro Roberto Almeida; Marino, Regina Helena (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to evaluate the antagonistic potential of endophytic bacteria isolated from 'Cereja Vermelho', 'Rasteiro Rio Grande', and 'Chapolin' tomato seedlings against the ALT23 Alternaria sp. fungus. Of the 23 endophytic isolates obtained, 12 were selected due to their greater effect on the mycelial growth of ALT23. Antagonism was tested in a completely randomized design, with 13 treatments (ALT23 and 12 isolates), with four replicates. The selected endophytic bacteria inhibited from 29.8 to 64.2% of the mycelial diameter and from 33.7 to 72.4% of the growth rate of ALT23.